Makna Referensial Pada Kritikan Di Situs Ngomikmaksa dan Relevansinya Sebagai Bahan Ajar Di SMA - Priatmie, Tivany Inggar; Dra. Atiqa Sabardila, M. Hum., Dra. Atiqa Sabardila, M. Hum (2016)
The purpose of this study are: (1) describe the referential meaning Ngomikmaksa sites. (2) determine the image description Ngomikmaksa criticism on the site. (3) know the relevance of referential meaning and drawing criticism as teaching materials Indonesian language learning in high school. Collecting data using techniques of documentation and technical notes. The method used to analyze data is unified method intralingual subtype referential with advanced engineering techniques Pilah Element Qualifier (PUP), the second match ekstralingual data analysis with advanced technique appeal something equalizing circuit (HBPS), and the third using constant comparison analysis techniques. According to the research, there are three conclusions: based on the results of research on referential meaning in his criticism on the site Ngomikmaksa there is some form of reference, namely the iconic sinsign, icon argument, iconic legsign, rhematic indexical sinsign, rhematic indexical legsign, dicent indexial legsign, rhematic symbol, dicent symbol , and punctuation symbols. From the analysis, it is known that the reference or the sign of the most widely used is the iconic sinsign. The overall meaning of all the data that has been collected is a form of representation of factual events in Indonesia are experiencing inequality, and injustice. Relations in learning criticism (text anecdotes) in the Indonesian language usage was polite when giving a criticism. Pictures of criticism that has been given on the site Ngomikmaksa encourage Shiva understand ethics in providing such criticism, using a logical reason, the language must be polite, and give of a solution.